Motywacje do wyjazdu, praca, więzi społeczne i plany na przyszłość polskich migrantów przebywających w Wielkiej Brytanii i Irlandii - Maciej Milewski; Joanna Ruszczak-Żbikowska (University of Warsaw, Centre of Migration Research (CMR), 2008)
– Post accession migration movements into UK and Ireland have been recognized in Poland as an important social issue. The scale of the departures also makes the problem increasingly important for social researchers. This paper attempts to recognize dynamics of the migration process taking into account the duration of migration project, migration motives, labour market positions of polish migrants in the UK and Ireland, characteristics of social relations and plans for the reverse migration. Data reported in this paper have been collected from online survey. Methodological background of the study argues this data collection technique can be regarded as an alternate source of information on polish citizens migration movements we have been observing lately. The most important argument supporting this thesis is the similarity of demographic profiles of polish internet users and polish migrants leaving country after EU accession, especially those who choose the UK and Ireland as their destinations.
Keywords: 330; Internationale Migration; Migranten; Polen (Personen); Großbritannien; Irland